Fundraising Strategy Analysis For Orphans And Du'afa Non-Profit Yabara Foundation Sidoarjo - Syaifudin Zuhri; Rozaqul Arif (Jurnal Indonesia Sosial Teknologi, 2023)
In Islam, doing good to anyone is ordered, because whoever wants to do good, is one of the lucky ones. This good deed includes amar ma'ruf which will have an impact on positive values and bring benefit both in this world and the hereafter. One of them is that we are encouraged to care for orphans and dhua'fa (weak economic groups), anyone who cares about this group apart from the rewards he gets will get great benefits. This research will analyze how the Fundraising Strategy for Orphans and Dhu'afa is carried out by the Yabara Foundation Sidoarjo, a foundation that cares for and often supports orphans and the du'afa. Through routine quarterly programs and annual Muharram moments, fundraising activities are driven by involving the community. The subject of this research is the Babussalam Bhayangkara Foundation (Yabara Foundation) Sidoarjo. This study uses a descriptive qualitative approach with primary and secondary research sources. Data collection techniques use observation, interviews, and documentation. The results of the research show that the fundraising strategy analysis was carried out in two ways 1). Mobilizing instrument fundraisers from foundation institutions that are in contact with residents 2) applying direct or indirect indicators. The result can be felt by the weak, especially orphans and the du'afa with a reduced economic burden that must be borne